الاستثمار في رأس المال المخاطر : دراسة حالة جمعية رأس المال المخاطر والملكية الخاصة البريطانية مع نموذج مقترح للتطبيق في العراق - الخياط، زهراء صالح حمدي (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2014)
يهدف البحث إلى التعريف برأس المال المخاطر كمفهوم وبديل مستحدث في مجال التمويل والاستثمار على حد سواء وإمكانية تطبيقه في العراق مع الإشارة إلى تجارب بعض الدول الغربية والعربية والاستفادة منها، فالبعض منها مرت على تجربتها أكثر من ربع قرن والبعض الآخر ما زال يحبو ولم تبلغ مرحلة النضوج بعد كالدول العربية. فضلا عن تقديم تحليل لجمعية رأس المال المخاطر والملكية الخاصة البريطانية كونها من أهم الجمعيات المتخصصة في أوروبا بالتركيز على مجال الاستثمار في المملكة المتحدة مقارنة ببقية دول العالم والتأكيد على أهمية وجود شركات وجمعيات متخصصة في مجال الاستثمار برأس المال المخاطر كونها توفر المعلومات عن حجم المبالغ المستثمرة في مختلف المشاريع والمناطق الجغرافية ولمختلف مراحل التمويل وطرق الخروج من المشاريع. يوصي البحث بضرورة بناء سوق مالي قوي وتوفير أدوات مالية تساهم بظهور وإدامة رأس المال المخاطر على هيأة سوق العراق للأوراق المالية طرح دليل للمستثمر لتعريفه برأس مال المخاطر وأهميته. The current research aims at investigating the adventurous capital as a modern concept and alternative in financing and investment field on equally and the possibility of applying it in Iraq, as well as, referring to experiments of some western and Arabs countries, and making use of it. Whereas, some of them their experiments for to more than (25) years, others are still crawling but they do not reach to the ripeness like the Arabs countries. Besides presenting an analysis for British adventurous capital association for being one of the most important specialized associations in Europe in focusing on investment field in the United Kingdom in comparison with the rest of world countries, also emphasizing on the importance of the existence specialized companies and associations in investing with adventurous capital for saving the information about the size of the invested capital in different projects and geographical areas and for different financing stages and the methods followed to get out from the projects. The researcher is recommending the necessity of forming a strong financial market and providing a financial tools participate in displaying and sustaining the adventurous capital on Baghdad Stocks Body, and floating a guide for the investor to inform him with the adventurous capital and its importance.
Keywords: الاستثمار -- التمويل -- رأس المال المخاطر -- شركات رأس المال المخاطر -- جمعية رأس المال المخاطر والملكية الخاصة البريطانية -- العراق